Novel genotype of mevalonic aciduria with fatalities in premature siblings. Issue 1 (1st January 2004) - Raupp, P; Varady, E; Duran, M; Wanders, R J A; Waterham, H R; Houten, S M
Abstract : Mevalonic aciduria is described in two very low birthweight siblings with unspecific clinical signs and recurrent septicaemia. Both died within the first 2 months of life. DNA analysis showed a novel mutation in the gene encoding mevalonate kinase.